Real-Time Monitoring-Based Stability Analysis of an Extra-Large LNG Tank Roof Under Construction - Yong Yang; Tuanhai Chen; Kezheng Zhang; Yu Song (Sensors)
The predominant failure mode of ultra-large LNG tanks is buckling. Current stability analysis methods for the roofs of these tanks face challenges, such as inaccurate buckling load simulations and on-site monitoring data scarcity. This article presents a novel method for analyzing buckling, systematically investigating the key factors and mechanisms affecting roof stability based on real-time monitoring during construction. Firstly, a method including the “element birth and death” technique is proposed for roof stability calculation, and its accuracy is validated through real-time monitoring data. Secondly, the roof stability at each construction stage is analyzed. Finally, the impact of three key structural parameters is explored. The results indicate that the “element birth and death” technique can accurately simulate roof stability under construction conditions. The roof plate thickness, beam cross-sectional dimensions, and rise–span ratio all have a positive influence on stability. Among the factors considered, the section size of the longitudinal beam and the rise–span ratio have the most significant impact on roof stability, followed by the section size of the circular beam. In terms of material consumption, enhancing roof stability by increasing the rise–span ratio is an effective option.